Essential Oil of Javanese Turmeric (Curcuma xanthorrhiza, Roxb) Decrease Level of LDL-Cholesterol and Body Weight In Rats - Endang Darmawan; Suwijiyo Pramono (Indonesian Society for Cancer Chemoprevention, 2016)
The aim of the present study was to investigate the effect of the essential oil of Javanese turmeric (Curcuma xanthorrhiza, Roxb) on level of low density lipoprotein-cholesterol (LDL-C) and body weight in rats. The groups were induced by high fat diet for 30 days to produce hyperlipidemia. The rats were treated with essential oil 25 mg/kgBW and simvastatin 25 kg/kgBW for 30 days. The LDL-C and body weight were measured on day one before treatment, and on day thirthy of the treatment. The results showed that the essential oil decreased the level of LDL-C and body weight in rats.Keywords: Javanese turmeric, Curcuma xanthorrhiza, essential oil, lipoprotein, simvastatin